DEVELOPING ANALYTICAL AND ORGANIZATIONAL SKILLS OF FUTURE INSTRUCTORS IN PLANNING AND MANAGING SPORTS TRAINING - Khakimdjanova Kamola Bakhadirovna (Proximus Journal Publishing, 2025)
The professional preparation of future sports instructors increasingly requires the development of strong analytical and organizational skills, particularly in the context of planning and managing sports training processes. Contemporary sport science emphasizes evidence-based decision-making, systematic training design, and effective organizational control as essential components of instructional competence. This article examines the pedagogical mechanisms for developing analytical and organizational skills among future instructors within higher education sport science programs. The study focuses on the role of structured training planning, data-informed analysis of athletic performance, and organizational management of training sessions as key areas of professional development. Attention is given to the integration of theoretical knowledge with practical training tasks, enabling students to analyze training objectives, select appropriate methods, and organize training processes efficiently. The article highlights that analytical skills allow future instructors to evaluate physical preparedness, monitor progress, and adjust training loads, while organizational skills ensure the rational distribution of time, resources, and responsibilities during sports training. The research also identifies challenges in current training practices, including fragmented planning approaches, limited use of analytical tools, and insufficient emphasis on managerial competencies. The findings suggest that the systematic development of these skills requires a competency-based and practice-oriented educational model that incorporates simulation, reflective analysis, and supervised practical experience. The article underscores the importance of pedagogical universities in preparing future instructors capable of managing complex training environments and responding flexibly to changing conditions. The results contribute to a deeper understanding of how analytical and organizational competencies can be effectively developed to enhance the quality and efficiency of sports training management
Keywords: analytical skills; organizational skills; future instructors